Research of Design and Control Strategy of Power Coupling Mechanism for Dual-motor Electric Vehicle - Wang Fei Wang Tie Wu Zhifei (Jixie chuandong)
A dual planetary row and dual motor coupling mechanism is proposed to solve the problems of low power per unit mass， low power at low speed and low utilization rate of high speed and low torque in single motor electric vehicles. Firstly， the dynamics analysis of the new coupling mechanism is carried out. The parameters of a dual-motor electric vehicle are matched to analyze the coupling characteristics of the two motors. Secondly， the control strategy is designed based on the required torque， speed， acceleration and motor efficiency. Finally， the corresponding driving module and control strategy module are built in Matlab/Simulink according to the mathematical model of each part of the vehicle， and the mathematical simulation is carried out. The results show that， in terms of power performance， the new dual planetary platoon power coupling structure and control strategy can meet the driving requirements of low-speed， high-speed and high-power vehicles， and also play a positive role in improving the economic performance of electric vehicles.